Manajemen Social Capital Pendidikan Islam Era Digital dalam Upaya Peningkatan Kepercayaan Publik dan Partisipasi Sosial - Ribhil Mafatih; Nur Hidayati (Universitas Negeri Malang, 2026)
Abstract: This study examines the management of social capital in Islamic educational institutions in the digital era, focusing on the role of media-based da’wah programs, particularly religious reality shows, in building public trust and enhancing social participation. Using a qualitative literature study design, data were obtained from primary journal articles, academic books, and research reports, and analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings reveal that digital social capital is constructed through three core dimensions “bonding”, “bridging”, and “linking”, which collectively shape the foundation of social cohesion in digital spaces. The results also indicate that religious reality shows strengthen public trust through host credibility, transparent program documentation, and emotional narratives that create a sense of closeness between audiences and institutions. Public trust subsequently functions as a form of social currency, encouraging community involvement in social activities, donations, and educational support. The study concludes that digital da’wah serves as a strategic instrument for reinforcing social capital and sustaining the development of Islamic educational institutions. The implications highlight the need for professional, transparent, and literacy-based digital media governance to maintain institutional legitimacy and increase public participation. Keywords: Digital Social Capital, Media Da’wah, Public Trust, Social Participation, Islamic Education Management. Abstrak: Penelitian ini menganalisis manajemen social capital lembaga pendidikan Islam pada era digital dengan fokus pada peran program dakwah media, khususnya religious reality show, dalam membangun kepercayaan publik dan meningkatkan partisipasi sosial. Melalui pendekatan kualitatif berbasis studi literatur, data diperoleh dari artikel jurnal primer, buku akademik, dan dokumen penelitian yang dianalisis menggunakan model Miles dan Huberman melalui proses reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa social capital digital terbentuk melalui tiga dimensi utama, yaitu bonding, bridging, dan linking, yang membentuk landasan kohesi sosial di ruang digital. Temuan juga mengungkap bahwa reality show dakwah mampu memperkuat public trust melalui kredibilitas host, transparansi kegiatan, dan narasi emosional yang mendekatkan audiens dengan lembaga. Kepercayaan publik kemudian berfungsi sebagai social currency yang mendorong keterlibatan masyarakat dalam kegiatan sosial, donasi, dan dukungan program pendidikan. Penelitian ini menyimpulkan bahwa dakwah digital dapat menjadi instrumen strategis bagi penguatan social capital serta keberlanjutan lembaga pendidikan Islam. Implikasi penelitian mendorong perlunya tata kelola media digital yang profesional, transparan, dan berbasis literasi sosial agar lembaga mampu mempertahankan legitimasi dan meningkatkan partisipasi publik. Kata Kunci: Social Capital Digital, Dakwah Media, Kepercayaan Publik, Partisipasi Sosial, Manajemen Pendidikan Islam